Recurrent/Intermittent Vaginal and Rectal Chlamydial Infection Following Treatment: A Prospective Cohort Study Among Female Sexually Transmitted Disease Clinic Patients. (12th March 2019) - Khosropour, Christine M; Soge, Olusegun O; Suchland, Robert; Leipertz, Gina; Unutzer, Anna; Pascual, Rushlenne; Hybiske, Kevin; Barbee, Lindley A; Manhart, Lisa E; Dombrowski, Julia C; Golden, Matthew R
Abstract: Background: Rectal Chlamydia trachomatis (CT) is common among clinic-attending women, but little is known about clearance and health implications of rectal CT. Methods: At the municipal sexually transmitted disease clinic in Seattle, Washington, in 2017–2018, we enrolled women at high risk for urogenital CT into an 8-week prospective study. Women received standard CT treatment at enrollment. Women self-collected daily rectal and vaginal specimens for nucleic acid amplification tests (NAATs) and completed weekly sexual exposure diaries. We performed CT culture on the enrollment rectal specimen. Results: We enrolled 50 women; 13 (26%) tested positive for vaginal (n = 11) and/or rectal (n = 11) CT. Sixty percent of women with rectal CT per NAAT were also culture positive. Median time to CT clearance after azithromycin treatment was 8.0 days for vaginal CT and 7.0 days for rectal CT. Eight women with rectal CT at enrollment had at least 1 rectal CT-positive NAAT after clearance of the initial infection; none reported anal sex. Conclusions: Most NAAT-positive rectal infections were culture positive, suggesting active infection. Time to NAAT clearance of rectal and genital tract CT was similar, and intermittent rectal CT positivity was common in the absence of anal sexual exposure. The cause of recurrent/intermittent rectal CT and the clinical implications of these infections require further study. Abstract : Among women at high risk for Chlamydia trachomatis (CT) followed for 8 weeks, median time to clearance after azithromycin was 8.0 days for vaginal (n = 7) and 7.0 days for rectal (n = 8) CT. Intermittent positive tests after initial clearance were common.